2010
DOI: 10.1007/s00330-010-1871-y
|View full text |Cite
|
Sign up to set email alerts
|

How safe is the use of ultrasound-guided cutting needle biopsy in the head and neck?

Abstract: CNB is a safe and reliable technique in the majority of cases but its risks in the head and neck are not negligible due to the proximity of major neurovascular structures and airways. We recommend special attention after neck surgery and radiotherapy and when the target is not clearly circumscribed and is close to major vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…There are, however, only a few studies on the use of tru-cut biopsy in the head and neck areas. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…There are, however, only a few studies on the use of tru-cut biopsy in the head and neck areas. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, this technique has been used for many years in lung [5], liver [3], breast [4], lymph nodes [6] and kidney [7] biopsies. However, there are only a few studies related to the use of CNB in head and neck regions [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, some authors have reported high success rates concerning the use of CNB taking into account that this method provides adequate biopsy samples for an accurate histological diagnosis [8,13]. Therefore, this pilot study aimed to evaluate the effectiveness of cutting needle biopsy in the diagnosis of solid oral lesions.…”
Section: Introductionmentioning
confidence: 99%